Reproduction in Sepia aculeata Van Hasselt, 1835 along the Andhra Pradesh coast, off the western Bay of Bengal - Felix, Jasmin; Muktha Menon; Shubhadeep Ghosh; Latha Shenoy (Indian Journal of Fisheries, 2023)
Sepia aculeata Van Hasselt, 1835 is a commercially important cuttlefish in Indian seas with limited studies on its biology from the Indo-Pacific region. This study, observed the reproductive biology of S. aculeata from samples landed by the trawl fishery operating off the coast of north Andhra Pradesh, off the western Bay of Bengal. A total of 3511 samples were studied, of which 2241 were females having dorsal mantle length (DML) ranging from 8.7 to 21.4 cm and weight from 78 to 901 g and 1260 were male specimens of DML ranging from 7.9 to 21.9 cm and weight from 54 to 738 g. Females dominated the landings with a sex ratio of 1.78. The length at first maturity was estimated at 14.3 and 12.6 cm DML for females and males, respectively. Both sexes spawned throughout the year with two significant peaks from July to October and from December to February with minor intermittent peaks. The absolute fecundity ranged from 330±1.44 x 102 eggs, with a relative fecundity of 75±8.94 x 102 eggs 100 g-1 body weight. The results of this study may be used as inputs in assessing the stock of S. aculeata in the study region. Keywords: Cephalopods, Needle cuttlefish, Size at first maturity, Spawning season, Trawl fisheries